PSYCHOLOGICAL REHABILITATION AFTER HYSTERECTOMY. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
Hysterectomy — the complete or partial surgical removal of the uterus is one of the most frequently performed gynecological procedures worldwide. This operation is often indicated in life-threatening conditions such as uterine cancer, large fibroids, or severe hemorrhaging. However, beyond its physiological consequences, hysterectomy also significantly impacts a woman's psychological well-being. Therefore, psychological support plays a critical role in the postoperative rehabilitation process. This article aims to substantiate the importance of psychological assistance during the rehabilitation period following hysterectomy.